2008
DOI: 10.1097/meg.0b013e328300a363
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte esterase reagent strips for the diagnosis of spontaneous bacterial peritonitis: a systematic review

Abstract: The reported incidence of spontaneous bacterial peritonitis (SBP) is 7-30% per annum in cirrhotic patients. Timely diagnosis and treatment is crucial to reduce mortality owing to this infection. Recently, leucocyte esterase reagent strips have been tested in the diagnosis of infection in the ascitic fluid. The objective was to evaluate the diagnostic value of leucocyte esterase reagent strips in SBP in cirrhotic patients with ascites, by systematically reviewing the evidence from prospective clinical studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Two recently published systematic reviews have pointed the heterogeneity in the number of patients included in each study, the AF samples tested and SBP episodes observed, as well as in all measures of LERS performance. 25,26 The other limitations of the RS test include the possibility of inter-observer variation in matching of color. There is dichotomy of opinion regarding the use of LERS test in SBP.…”
Section: Uriscanmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recently published systematic reviews have pointed the heterogeneity in the number of patients included in each study, the AF samples tested and SBP episodes observed, as well as in all measures of LERS performance. 25,26 The other limitations of the RS test include the possibility of inter-observer variation in matching of color. There is dichotomy of opinion regarding the use of LERS test in SBP.…”
Section: Uriscanmentioning
confidence: 99%
“…25 However, because of the consistently excellent NPV (>95% in the majority of the studies) of LERS, others have advocated its place in the ascitic tap diagnostic algorithm specially as a preliminary screening tool for SBP diagnosis. 26,27 The reagent strip has several advantages, such as: it is easy to use, there is no need of expertise for matching of color, and very rapid (takes 90-120 s). With use of bedside LERS test early antibiotic therapy can be started in a fair percentage of asymptomatic SBP patients.…”
Section: Uriscanmentioning
confidence: 99%
“…Also, only 50 to 70% of a patient's positive cultures for ascetic fluid are generally reported (9)(10)(11). Due to limitations such as the time-consuming process for the diagnosis of peritonitis ascetic fluid and the lack of access to appropriate laboratory facilities, reports of negative cultures could be delayed (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of urinary dipstick (leukocyte esterase detection resulting from activated neutrophils) has been proposed to reach such targets, but as they were originally developed for use in urinary tract infection the cut-off values are different and the number of false negative is high. Nevertheless, none of the recent guidelines recommends the use of these reagent test strips to assess leucocyte esterase activity of activated PMNs for the diagnosis of SBP owing to unacceptable diagnostic accuracy, mostly because of the high value of false negative results [46,[49][50][51][52] . Recently, a new reagent strip test has been calibrated for ascitic fluid with a cut-off of 250 PMN/mm 3 .…”
Section: Diagnosismentioning
confidence: 99%